TP53 wild-type/PPM1D mutant diffuse intrinsic pontine gliomas are sensitive to a MDM2 antagonist - Cheng Xu (BMC, 2021)
Abstract Diffuse intrinsic pontine gliomas (DIPGs) are high-grade tumors of the brainstem that often occur in children, with a median overall survival of less than one year. Given the fact that DIPGs are resistant to chemotherapy and are not amenable to surgical resection, it is imperative to develop new therapeutic strategies for this deadly disease. The p53 pathway is dysregulated by TP53 (~ 60%) or PPM1D gain-of-function mutations (~ 30%) in DIPG cases. PPM1D gain-of-function mutations suppress p53 activity and result in DIPG tumorigenesis. While MDM2 is a major negative regulator of p53, the efficacy of MDM2 inhibitor has not been tested in DIPG preclinical models. In this study, we performed a comprehensive validation of MDM2 inhibitor RG7388 in patient-derived DIPG cell lines established from both TP53 wild-type/PPM1D-mutant and TP53 mutant/PPM1D wild-type tumors, as well in TP53 knockout isogenic DIPG cell line models. RG7388 selectively inhibited the proliferation of the TP53 wild-type/PPM1D mutant DIPG cell lines in a dose- and time-dependent manner. The anti-proliferative effects were p53-dependent. RNA-Seq data showed that differential gene expression induced by RG7388 treatment was enriched in the p53 pathways. RG7388 reactivated the p53 pathway and induced apoptosis as well as G1 arrest. In vivo, RG7388 was able to reach the brainstem and exerted therapeutic efficacy in an orthotopic DIPG xenograft model. Hence, this study demonstrates the pre-clinical efficacy potential of RG7388 in the TP53 wild-type/PPM1D mutant DIPG subgroup and may provide critical insight on the design of future clinical trials applying this drug in DIPG patients.